The Relationship Between Knowledge and Attitudes of Mothers Who Attended the Mother and Toddler Class on Infant Nutritional Status at the Jatijajar Community Health Center Uptd in 2024 - Mutia Sari, Anggi Putri; Limbong, Tetty Oktavia; Raidanti, Dina (Journal of Nutrition and Public Health, 2026)
Background: Nutrition is a key component determining the quality of human resources. In Indonesia, in 2021, the incidence of malnutrition in toddlers was recorded at 1.0% and undernutrition at 3.9%. Mothers' knowledge and attitudes significantly impact the nutritional status of toddlers, thus various efforts are being made to address this, including the use of the KIA Handbook and the implementation of Mother and Toddler Classes. Aims: This study aims to determine the relationship between the knowledge and attitudes of mothers who attended the Mother and Toddler Class towards the nutritional status of infants at the UPTD Jatijajar Health Center. Methods:This study was a quantitative, observational, and analytical study with a cross-sectional approach. The sample consisted of 22 mothers and their babies, selected using saturation sampling. Result: Based on the Spearman's Rank Correlation Coefficient test, the results obtained between the maternal knowledge variable and the infant's nutritional status were Sig. (2-tailed) 0.591 (p > 0.05). Similarly, the maternal attitude variable and the infant's nutritional status showed Sig. (2-tailed) 0.591 (p > 0.05). Conclusion: It can be concluded that the knowledge and attitudes of mothers who attended the Mother and Toddler Class did not have a significant relationship with the nutritional status of infants at the UPTD Jatijajar Health Center in 2024.